Molecular Characterisation of Bacteriocinogenic Lactobacillus Plantarum Isolated from Malaysian Fermented Food - Moghadam, Morteza Shojaei (2009)
Molecular approaches were used in this study to characterize six bacteriocinogenic Lactobacillus plantarum strains isolated from Malaysian foods since biochemical approaches could not differentiate them distinctively. The Lb. plantarum strains were initially identified as Lb. plantarum I with 99.9% similarity by the analysis of carbohydrate fermentation pattern using API CHL50 identification kit. The biochemical identification result was further confirmed by analyzing partial sequence of 16S rDNA that showed 99-100% similarity to Lb. plantarum. Identification up to genus level was also achieved when Amplified Ribosomal DNA Restriction Analaysis (ARDRA) was applied with Lactococcus lactis MG1363, Lb. plantarum ATCC 11305, Lb. johnsonii, Streptococcus thermophilus BAA 250 and Pediococcus acidilactici 446 as reference strains. Furthermore, the studied Lb. plantarum strains were characterized using genotypic methods: plasmid profiling, randomly amplified polymorphic DNA (RAPD), polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP), repetitive extragenic palindromes (Rep)-PCR as well as 16S-23S rDNA (ITS1) and 23S-5S rDNA (ITS2) spacer regions analyses. The strain RG14 was successfully differentiated from others by plasmid profiling. Results from RAPD study in which 6 arbitrary primers were tested, revealed slight differences in the genome of six Lb. plantarum strains. Moreover, sequence analysis of ITS1 revealed a four base pair variable region from which the strains could be divided into four groups. Comparative analysis of ITS1 with 17 Lb. plantarum strains available in GenBank confirmed the variability of this region and showed that the genotype of the studied strains are not present in the strains used for comparative analysis. As for PCR-RFLP study, the studied strains were initially screened for the presence of structural bacteriocin genes. It was found that all studied strains harboured the novel combination of plantaricin EF (Pln EF) and plantaricin W (Pln W), which had not been reported elsewhere. However, the PCR-RFLP technique was not discriminative when the Pln EF genes were digested with restriction enzymes HindIII, MboI and PstI. Although rep-PCR showed strong typing ability, the banding pattern was not discriminative. The ITS2 region showed an extra 5S rDNA sequence downstream of the ribosomal DNA region. The ITS2 region, however, was highly conserved among the strains and encodes rRNA that form secondary structure with the predicted free energy of -11.5 Kcal/mol. In conclusion, the studied strains are novel bacteriocinogenic Lb. plantarum, which were successfully discriminated in a polyphasic approaches using plasmid profiling, RAPD and ITS1 analysis with the RAPD technique showing the highest discriminatory power.